2012
DOI: 10.1504/ijeg.2012.047443
|View full text |Cite
|
Sign up to set email alerts
|

Technology and the quality of public deliberation: a comparison between on and offline participation

Abstract: International audienceThe empirical turn in deliberative democracy has recently generateda considerable amount of academic work. Scholars have tried to operationalisethe theoretical dimensions of deliberative democracy into robust criteria inorder to evaluate the quality of public discussion. Few of them however havesystematically compared online and offline deliberation to analyse the link between the technological formats deployed in a deliberative procedure and thequality of the discussion. This is what th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 37 publications
0
24
0
3
Order By: Relevance
“…The theoretical complexity of inclusiveness is reflected in empirical research. Although some studies focus on the share of voice to investigate the potential domination by a few users (Stromer-Galley, 2007), others investigate the diversity of socioeconomic characteristics among participants, such as age, gender, or education (Monnoyer-Smith & Wojcik, 2012). Overall, these studies have found that the diversity in comment sections is low and comparatively few users write a high share of comments (Blom, Carpenter, Bowe, & Lange, 2014; Diakopoulos & Naaman, 2011).…”
Section: The Deliberative Quality Of User Comments and Discussionmentioning
confidence: 99%
“…The theoretical complexity of inclusiveness is reflected in empirical research. Although some studies focus on the share of voice to investigate the potential domination by a few users (Stromer-Galley, 2007), others investigate the diversity of socioeconomic characteristics among participants, such as age, gender, or education (Monnoyer-Smith & Wojcik, 2012). Overall, these studies have found that the diversity in comment sections is low and comparatively few users write a high share of comments (Blom, Carpenter, Bowe, & Lange, 2014; Diakopoulos & Naaman, 2011).…”
Section: The Deliberative Quality Of User Comments and Discussionmentioning
confidence: 99%
“…Thus, logic would state that online discussion venues built on principles from deliberative theory – and thus employing facilitated deliberation – would be more likely to bring about discussions with beneficial outcomes for democracy than normal everyday online discussion (e.g. Manosevitch, 2010; Smith and Wojcik, 2012). Early evidence from experiments in online deliberation (see Strandberg and Grönlund, 2014 for indepth review) indeed lends some support for this notion of beneficial effects stemming from democratic design of online discussion between citizens.…”
Section: Modality – the Online Realm As A Venue For Deliberationmentioning
confidence: 99%
“…Design choices concerning participant interaction are key because a basic deliberative discourse feature is the opportunity for participants to "exchange opinions as well as incorporate and respond to others' viewpoints" (Wilhelm, 2000, p. 88). With this in mind, researchers have contrasted face-to-face versus computer-mediated interaction designs (Baek et al, 2012;King, Hartzel, Schilhavy, Melone, & McGuire, 2010;Monnoyer-Smith & Wojcik, 2012;Pedrini, 2014;Tucey, 2010) and explored variations in online formats (Davies & Chandler, 2012;Shaw & Benkler, 2012;Towne & Herbsleb, 2012).…”
Section: The Civic Utility Of Variable Media Richnessmentioning
confidence: 99%